2018
DOI: 10.29407/js_unpgri.v4i1.12092
|View full text |Cite
|
Sign up to set email alerts
|

Persepsi Guru Pamong Terhadap Kualitas Mahasiswa Calon Guru PJOK Saat Melaksanakan Program Pengelolaan Pembelajaran di Sekolah Mitra

Abstract: This study aims to determine the quality of prospective PE teachers (PPET) in implementing learning management program (LMP) in a partner school of Universitas Negeri Surabaya. Descriptive qualitative approach wa applied. The research subjects were ten PPET who conducted LMP. There were three criteria that would be assessed by the supervising teacher: (1) students’ feasibility to become a PE teachers; (2) need of teacher competence; and (3) competence in student teaching. Research findings showed that the aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
(6 reference statements)
0
4
0
2
Order By: Relevance
“…Teacher creativity can mediate the influence of Human Resource Management (HRM) practices that schools can do to improve teacher performance (Muzakki et al, 2021). Great physical education teachers have qualified academic abilities, master the latest curriculum developments, master teaching materials, have good classroom management skills, have skills to solve learning problems, and are creative and innovative (Khory et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Teacher creativity can mediate the influence of Human Resource Management (HRM) practices that schools can do to improve teacher performance (Muzakki et al, 2021). Great physical education teachers have qualified academic abilities, master the latest curriculum developments, master teaching materials, have good classroom management skills, have skills to solve learning problems, and are creative and innovative (Khory et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Instrumen dalam penelitian ini yang digunakan adalah pedoman wawancara terstruktur untuk mengungkap kualitas SSB dari sisi pengelolaan (Kristanto & Darni, 2018) dan sumber daya manusia yang tersedia (Rohman, 2017). Pada pertanyaan yang membutuhkan keputusan yang bersifat kuantitatif digunakan skala nilai dengan rentang 0-10 sesuai dengan teori skala respon ekspektasi yang hasilnya akan dianalisis menggunakan statistik deskriptif (persentase dan mean) (Khory et al, 2018). Sedangkan hasil wawancara yang bersifat terbuka, dianalisis menggunakan empat tahap yaitu tabulasi data, reduksi data, penyajian data dan verifikasi/simpulan (Sugiyono, 2006).…”
Section: Metode Penelitianunclassified
“…The study was conducted to evaluate students in educational and noneducational departments, which shows no difference in teaching and learning effectiveness based on teachers' backgrounds. However, the quality of the learning process carried out by the physical education students during the internship is in the excellent category have various abilities in mastering curriculum, sports, and science in teaching (Khory et al, 2018). Then, it can be concluded that advanced monitoring on the quality of internships has not been concerned yet, especially in terms of the students' quality and the learning effectiveness.…”
Section: Introductionmentioning
confidence: 99%